1989
DOI: 10.1055/s-2007-1020309
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Coagulation and Fibrinolytic Systems During and After Cardiopulmonary Bypass Surgery

Abstract: Components of the coagulation and fibrinolytic systems were determined in patients undergoing open heart surgery with cardiopulmonary bypass. The variables studied included prothrombin, antithrombin-III, spontaneous plasmin activity, plasminogen and functional antiplasmin activity. The variables were measured using chromogenic peptide substrate assays. A marked, transitory, increase in spontaneous plasmin activity prior to cardiopulmonary bypass, but after heparin injection was found. A decrease in antiplasmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 0 publications
2
19
0
1
Order By: Relevance
“…This study confirms that adding heparin increases kallikrein-and plasmin-like activi ties in plasma [1,2]. Neutralizing the heparin with protamine reversed most of the enzyme activities, while aprotinin had little effect on the phenomenon.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This study confirms that adding heparin increases kallikrein-and plasmin-like activi ties in plasma [1,2]. Neutralizing the heparin with protamine reversed most of the enzyme activities, while aprotinin had little effect on the phenomenon.…”
Section: Discussionsupporting
confidence: 73%
“…Proteases activated after heparin injection in vivo [1,2] could also possibly split larger, natural substrates. This is supported by studies performed by Mosko witz et al [27], who found that heparin in duced formation of bradykinin from highmolecular kininogen in plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiplasmin levels do not return to normal for 48 to 72 hours postoperatively, whereas plasmin levels after discontinuation of CPB return to normal immediately (Kongsgaard et al 1989). Therefore, after CPB, the fibrinolysis activation is prolonged, which can lead to increased postoperative bleeding (Gelb et al 1996, Casati et al 2001, Linden 2003.…”
Section: Fibrinolysis During Cardiopulmonary Bypassmentioning
confidence: 99%
“…Fibrinolytic activity increases significantly during and following CPB because of intraoperative contact activation, release of tissue plasminogen activator due to kallikrein production, use of relatively high-dose heparin, and inhibition of α2-antiplasmin (Kongsgaard et al 1989, Ray et al 1994, Altman et al 1998. Antiplasmin levels do not return to normal for 48 to 72 hours postoperatively, whereas plasmin levels after discontinuation of CPB return to normal immediately (Kongsgaard et al 1989).…”
Section: Fibrinolysis During Cardiopulmonary Bypassmentioning
confidence: 99%